Academic Management Strategies of English Program School Under Office of the Private Education Commission (OPEC): Bangkok District - Singklieng, Sirikhwan; Sikkhabandit, Sowwanee; Sriprasertpap, Khwanying (Rajapark Journal, 2022)
The purpose of this research was to develop strategies for the academic administration of schools that provide teaching and learning according to the Ministry of Education’s English Program. The research was quantitative and qualitative and was conducted in 3 steps: 1. Study the current conditions, desirable conditions, and necessities for academic administration of schools that provide teaching and learning in accordance with the Ministry of Education’s curriculum in English Program; 2. Create a strategy for academic administration of schools that provide teaching and learning in accordance with the Ministry of Education’s curriculum in English Program; and 3. Experiment and evaluate the feasibility and usefulness of the academic management strategies of schools that provide teaching and learning according to the Ministry of Education in English Program statistics used in the analysis, namely, percentage, mean, and ordinal demand index value, standard deviation, and content analysis. The results of the research revealed that the academic administration of schools that provide teaching and learning in accordance with the Ministry of Education’s curriculum is in the English Program. The present condition and the desirable condition were at the highest level. The development of the learning process is the first and most demanding area. Strategies for academic administration of schools that provide teaching and learning in accordance with the Ministry of Education’s curriculum in the English Program, consist of 5 main strategies: 1) developing a learning process; 2) development of educational institutions’ curriculum; 3) development of innovative media and educational technology; 4) measurement, evaluation, and transfer of learning outcomes; and 5) research to improve educational quality.